Economic policy uncertainty and the founding family firm premium - Fütterer, Markus; Rapp, Marc Steffen; Requejo, Ignacio (Journal of Corporate Finance, 2026)
Studying a monthly panel of European listed non-financial firms, we document a negative effect of economic policy uncertainty (EPU) on firm value but a positive effect on the valuation premium of founding family firms. These findings are confirmed in a propensity score–matched sample and remain robust to a battery of tests addressing omitted variable bias and measurement error. The lower EPU-sensitivity of founding family firms is concentrated in politically connected firms operating in low-corruption environments. Additional analyses show that founding family firms' valuation premium is more pronounced for R&D-intensive firms with less diversified and less labor-intensive business models. Overall, our results support the view that founding family firms are more resilient to uncertainty and may contribute to economic stability.